Gelar Habib: Menelisik Eksklusivitas, Kontroversi, dan Jalan Keluar Menurut Al-Qur'an - Ahmad Aziz Masyhadi; Tasmuji Tasmuji (Pusat Riset dan Inovasi Nasional, 2023)
The controversy surrounding the lineage of Habibs has recently become increasingly widespread and even sparked debates that have led to hatred within society. This issue is often exploited to exacerbate differences, potentially damaging Islamic brotherhood. Therefore, a wise middle ground is needed to prevent discussions about lineage from becoming increasingly wild and divisive. One important solution is to return to the teachings of the Quran. This holy book provides comprehensive guidelines on morality, brotherhood, and the principles of human equality. The Quran emphasizes that a person's honor in the sight of God is not determined by ancestry, social status, or nationality, but by their level of piety. This message is universal and relevant to all humanity, regardless of background. Piety itself is born from a transcendental moral awareness and is manifested through righteous and beneficial behavior. Therefore, Muslims should focus more attention on character development and self-improvement, rather than pride in lineage, which only fuels controversy with no real benefit to social life.